Statistical Relations Between Ionospheric Conductance and Precipitating Electrons Derived From Direct Conjugate Observations - Longxing Ma; Xingbin Tian; Yiqun Yu; Linhui Tang; Jinbin Cao (Space Weather)
Abstract Ionospheric conductance represents a pivotal aspect of the magnetosphere‐ionosphere coupling process. Although widely applied, the well‐known Robinson 1987 formula relating precipitation to ionospheric conductances was challenged due to its limited database. In this study, we revisit the relationship using a comprehensive data set of ∼2,400 conjugate events. Each event includes ionospheric conductances calculated based on the electron density measurements from the Poker Flat Incoherent Scattering Radar (PFISR) and precipitating electron flux detected directly by the Defense Meteorological Satellite Program (DMSP) at conjugate locations. Results reveal that both Hall and Pedersen conductances follow power‐law relationships with precipitating energy flux. However, the average energy of precipitating electrons, reported as a traditional dependency in previous models, does not exhibit clear relationships with the conductances, especially if data samples during geomagnetic activities are included. Future studies may need to investigate the dependence of conductances on more factors.